Pengaruh Model Pembelajaran RQA (Reading, Questioning Dan Answering) Terhadap Pemahaman Konsep IPA Siswa Kelas V SD Muhammadiyah 02 Cimanggu - Pebri Isnawati; Enggar Estiwi (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2025)
This study aims to determine the effect of the RQA (Reading, Questioning, and Answering) learning model on the science concept comprehension of fifth-grade students at SD Muhammadiyah 02 Cimanggu. The research method used is pre-experimental with a One Group Pretest-Posttest design involving 24 students. Data collection was carried out through tests, observations, and documentation, with tests as the main instrument. Data analysis used a quantitative approach through comparison of pretest and posttest, followed by normality test, homogeneity test, and paired samples t-test at a 5% significance level. The results show that the average posttest score of 72.0286 is higher compared to the pretest score of 64.3216. The hypothesis test using a paired samples t-test at a 5% significance level yielded a sig. value of 0.016, which is smaller than 0.05. This indicates that the RQA (Reading, Questioning, and Answering) learning model has a significant effect on improving the science concept understanding of fifth-grade students at SD Muhammadiyah 02 Cimanggu. This study has limitations in the use of a design without a control group, a limited number of subjects, and a relatively short research duration. Therefore, it is recommended that future research involve a larger sample, use a stronger experimental design, and extend the research duration so that the results obtained are more comprehensive and generalizable.